2018
DOI: 10.1038/s41598-018-33908-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and in vitro biological evaluation of two matrine derivatives

Abstract: Matrine is a traditional Chinese medicine and botanical pesticide with broad biological activities, including pharmacological and agricultural activities. In present work, two matrine derivatives have been successfully synthesized via introducing indole and cyclohexylamino to 13 position of matrine, respectively, with sophocarpine as starting material, and structurally characterized via infrared spectroscopy(IR), MS, 1 H NMR, 13 C NMR and X-ray crystal diffraction. The results of the in vitro biological activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…Matrine is a naturally occurring heterocyclic compound derived from quinolizidine which is isolated from the roots of Sophora flavescens and Sophora alopecuroides (Fabales: Fabaceae) (Mao and Henderson, 2007; Zhang et al, 2012; Cheng et al, 2018). Matrine is known to have a wide range of medicinal activities like anti-cancer, anti-inflammatory, antimicrobial, antiviral, antifibrotic, and immunoinhibitory, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrine is a naturally occurring heterocyclic compound derived from quinolizidine which is isolated from the roots of Sophora flavescens and Sophora alopecuroides (Fabales: Fabaceae) (Mao and Henderson, 2007; Zhang et al, 2012; Cheng et al, 2018). Matrine is known to have a wide range of medicinal activities like anti-cancer, anti-inflammatory, antimicrobial, antiviral, antifibrotic, and immunoinhibitory, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the use of matrine in an isolated form or in a mixture with other botanical, synthetic and microbial pesticides to control different insect pests (termites, whiteflies, aphids, leaf hoppers, caterpillars and mites), fungal and bacterial diseases and nematodes in china (Yang and Zhao, 2006; Liu et al, 2007; Mao and Henderson, 2007; Li et al, 2010; Ali et al, 2017). Matrine has been commercialized under different trade names; however, their insecticidal activities are lower than the popular insecticides introduced by international pesticide companies during the last few years (Cheng et al, 2018). Based on the good biological activity and wide range it will be interesting to develop a practical strategy for preparation of insecticidal formulations in which matrine can be used in mixture with other natural pest control agents.…”
Section: Introductionmentioning
confidence: 99%
“…Matrine has also been used to control different insect pests of various crops [9]. Matrine is known to target insect acetylcholine receptors, which in turn affects acetylcholinesterase production [10]. Matrine has shown antifeedant activities against Formosan subterranean termites (Coptotermes formosanus Shiraki) and two spotted spider mites (Tetranychus urticae Koch) [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these characteristics, matrine is considered as a green/environmentally friendly insecticide [ 15 ]. Matrine has been commercialized under different trade names; however, its insecticidal activity is lower than the popular insecticides introduced by international pesticide companies during the last few years [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the special insecticidal mechanism of pyridalyl against lepidopterous larvae, 1,1-dichloropropene derivatives bearing structurally diverse substituted heterocycle rings that replace the pyridine ring of pyridalyl have been designed and synthesized, and the compounds displayed significant insecticidal activity against p rodenia litura and diamondback moths 20 . In addition, our previous studies showed that introducing carbon disulfide and cyclohexylamine groups can improve the toxicity of matrine to Lipaphis erysimi and Mulberry Root-Knot Nematode , while the introduction of indole and cyclohexylamine groups can increase the inhibition activity of matrine on Sf9 cell 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%